Advances in Pediatric Acute Promyelocytic Leukemia - Shannon E. Conneely; Alexandra M. Stevens (MDPI AG, 2020)
Acute promyelocytic leukemia (APL) is a rare disease accounting for only 5%−10% of pediatric acute myeloid leukemia (AML) and fewer than 1000 cases occur annually in the United States across all age groups. Characterized by t (15; 17), with a resultant PML-RARA gene fusion driving leukemia development, advances in therapy have improved outcomes for APL significantly in the past several decades, now making APL the most curable form of AML in both children and adults. Cure rates in APL are now comparable to pediatric B-lymphoid leukemias. The success of APL treatment is due, in part, to the breadth of understanding of the driver PML-RARA mutation as well as collaborative efforts to quickly introduce and maximize the benefit of new therapies. Here, we review the presentation, clinical features, pathogenesis, and treatment advances in pediatric APL.